STUDY OF CLINICAL AND FUNCTIONAL CHARACTERISTICS OF CHRONIC NON-SPECIFIC LUNG DISEASES PREVALENCE IN YOUNG PEOPLE - Кодиров Д; Ахмедов А.К (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Early identification of chronic obstructive pulmonary disease (COPD) in young individuals could be beneficial to attempt preventive interventions. The objective of this study was to investigate clinical features and outcomes of young individuals with COPD from the general population cohort.